Teaching and learning calculus using TI-NSPIRE - Parrot, M.A.S.; Leong, K.E. (2013)
Failure to understand abstract concept among students might lead to misconception in understanding Calculus. Using instructional activities in discovering mathematical concepts by integrating technology may be one learning style to suit their needs. This study explored the concept of Calculus by using TI-Nspire. It was conducted by using a case study research design. The participants of this study were three Form Five students from a mixed ability classroom of a public school in Selangor. Instructional activities were designed on teaching and learning of the component Calculus in SPM Additional Mathematics. Two selected students will be interviewed based on their responses from the post-test. In addition, this study will provide a better understanding in improving students’ skills in learning Calculus.